Św. Jan Chryzostom, O Dawidzie i Saulu. Homilia trzecia (CPG 4412: De Davide et Saule. Homilia tertia) - Libowski, Łukasz; Wilk, Piotr (Vox Patrum, 2022)
Translation into Polish of the work "De Davide et Saule. Homilia tertia" by John Chrysostom